Adaptation thresholds and pathways for tidal flood risk management in London - Hall, J; Harvey, H; Manning, L (Elsevier, 2019)
Protecting the UK's capital city from global mean sea level rise that the IPCC considers plausible over the next centuries would require a combination of a new tidal barrier, high volume pumping and incremental raising of the system of flood walls and embankments. Using a risk and decision analysis methodology that is transferable to other vulnerable coastal cities of high strategic economic and political importance, we quantify sequences of adaptations that would be needed to protect London from flooding by the sea to the year 2300. Two critical adaptation thresholds are identified: (i) when mechanical pumping has to be provided alongside the moveable tidal barrier in order to drain the River Thames and (ii) when a permanently closed barrier with pumping to remove all of the river flow becomes the only viable means of avoiding flooding. We test the sensitivity of the costs and benefits of alternative adaptation pathways to a wide range of sea level rise trajectories. The adaptation pathway that most cost-effectively and robustly maintains risk at a tolerable level involves moving the Thames Barrier 17 km towards the sea if mean sea level rises 2 m above present levels. Our methodology provides a quantitative risk-based implementation of an adaptation pathway.